STRATEGI PENGEMBANGAN DESA WISATA DI KAWASAN HINTERLAND GUNUNG BROMO JAWA TIMUR - Mujanah, Siti; Ratnawati, Tri; Andayani, Sri (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
The aims of this study is to find an effective strategy in the development ofHinterland Tourism Village in Mount Bromo area, so itwill becomes selfsufficientvillages and able to provide the facilities, infrastructure for local andforeign tourism. This research is include as Descriptive explanatory researchwich to obtain field data to build a model of the grand design of rural tourismdevelopment in the Hinterland region of Bromo Mountain. The Object of thisresearch are three tourist villages around Bromo Mountain, while datacollection was done by interviews with rural principiples, SMEs and bothtourist local and international as the sample respondents. Data were analyzedwith SWOT analysis to determine the strategy gathering an the other one isAnalytical Hierarchy Process (AHP) to determin the ranking of ODTW. Theresults of SWOT analysis based on the weight and value scores of respondentsindicate that the development of rural tourism was scored in the first quadrantis a strategy to optimize the strengths and opportunities, while the results showthat the AHP Wonokitri village has the highest number and the second isNgadisari and ranked third village is Ngadas village. The model of strategyrural tourism could developed when supported optimally by the community, thegovernment such as the Government Center for TNBTS, Department ofTourism, PU, Cooperatives and SMEs, and the Department of SocietyEmpowerement, while also supportby private sectors, SMEs and local investorsand also education Institutions.Keywords: Model Strategy, and Rural Tourism Development